2020
DOI: 10.1038/s41419-019-2214-9
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting alkaline ceramidase 3 alleviates the severity of nonalcoholic steatohepatitis by reducing oxidative stress

Abstract: Overload of palmitic acids is linked to the dysregulation of ceramide metabolism in nonalcoholic steatohepatitis (NASH), and ceramides are important bioactive lipids mediating the lipotoxicity of palmitic acid in NASH. However, much remains unclear about the role of ceramidases that catalyze the hydrolysis of ceramides in NASH. By analyzing the National Center for Biotechnology Information (NCBI) Gene Expression Omnibus (GEO) database, we found that alkaline ceramidase 3 (ACER3) is upregulated in livers of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…Oxidative stress, which can promote the injury of hepatocytes, has been proved to be a crucial pathological event for the progression of NASH (Wang et al, 2020). In this research, we found that MCD diet feeding significantly increased the levels of MDA in the liver, while PEA treatment obviously attenuated this elevation.…”
Section: Discussionmentioning
confidence: 50%
“…Oxidative stress, which can promote the injury of hepatocytes, has been proved to be a crucial pathological event for the progression of NASH (Wang et al, 2020). In this research, we found that MCD diet feeding significantly increased the levels of MDA in the liver, while PEA treatment obviously attenuated this elevation.…”
Section: Discussionmentioning
confidence: 50%
“…A very recent study showed that deficiency of ACER3 alleviates the pathogenesis of NASH by regulating the hepatic levels of C18:1‐ceramide. ( 30 ) It is intriguing that NcDase activity influences the composition of MUFAs and the reduction of particularly FA18:1 n‐9 and FA16:1 in the total lipid fraction in TG, CE, and PL fractions in NcDase −/− mice (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ultraviolet and H 2 O 2 treatment generates ceramide, which activates AMPK [58], while short-chain ceramides inhibit Nrf2 activation [34], and knock out of acid ceramidase 3 augments C18:1-ceramide levels, which alleviates early inflammation, oxidative stress, and fibrosis in a mouse model of NASH [59]. It has also been suggested that ceramide-activated AMPK can limit nutrient-induced stress and autophagy [60].…”
Section: Discussionmentioning
confidence: 99%